Competitive anxiety among university ten-pin bowlers - Tan, Hui Xian (Nanyang Technological University, 2021)
Competitive anxiety is a common phenomenon experienced by athletes of all ages and competitive levels. Competitive anxiety is divided into three dimensions: cognitive anxiety, somatic anxiety, and self-confidence. It can be attributed to many factors, with one being the athlete’s perception of their competitive anxiety. This perception of anxiety can be interpreted in two directions, facilitative or debilitative, with the former being associated with better performance. Technical sports in particular require athletes to consider many variables before execution, requiring high mental toughness. Minimal research was done on ten-pin bowling. This study aims to explore the relationship between competitive anxiety and performance in ten-pin bowlers and the role of experience in reducing debilitative anxiety levels. A cross-sectional study was conducted on 24 experienced bowlers (12F, 12M) [Mean (Standard Deviation (SD)); Age: 22.667 (2.697); Years of Competitive experience: 7.792 (4.191)] and 24 recreational bowlers (12F, 12M) [Mean (SD); Age: 22.250 (1.422); Years of competitive experience: 0], whereby they were tasked to play 2 bowling games (1 warm-up, 1 competitive). Competitive State Anxiety Inventory - 2 (directional) (CSAI-2d) was used to quantify their competitive anxiety levels prior to the competitive game against their allocated pseudo competitor. Athletes with lower self-confidence exhibited increased debilitative levels of both cognitive and somatic anxiety, compromising performance. However, comparing between the sample groups, despite no significant findings, higher anxiety levels and lower self-confidence were displayed for experienced bowlers. This may be due to the lack of competition in recent times. Additionally, no noticeable trends were found for the direction variables. In conclusion, this study could educate stakeholders on the impact competitive anxiety has on their performance and investigate strategies to adjust their anxiety perception.